2004
DOI: 10.1177/000348940411300407
|View full text |Cite
|
Sign up to set email alerts
|

Sphenoid Sinus Mucocele with Unilateral Blindness

Abstract: Mucoceles of the sphenoid sinus are rare and may frequently remain undiagnosed until symptoms due to compression of surrounding structures set in. In such cases, the optic nerve, because of its close proximity to the sphenoid sinus, is at risk, and pressure exerted by the mucocele may result in visual impairment. A case of a sphenoid sinus mucocele with sudden-onset unilateral blindness as the only presenting symptom has been described. Early diagnosis and prompt surgical intervention enabled the vision to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In man there are several recorded case histories, 5–15 with an extremely wide age incidence, presenting with symptoms of a transient visual disturbance, varying or progressing to complete irreversible blindness, unilateral or bilateral, and all due to sphenoid sinus involvement of varying causes. It is interesting, and significant, that the following three equine cases could easily be included in this human group.…”
Section: Introductionmentioning
confidence: 99%
“…In man there are several recorded case histories, 5–15 with an extremely wide age incidence, presenting with symptoms of a transient visual disturbance, varying or progressing to complete irreversible blindness, unilateral or bilateral, and all due to sphenoid sinus involvement of varying causes. It is interesting, and significant, that the following three equine cases could easily be included in this human group.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al concluded no significant correlation exists between the prognosis of visual acuity and early surgical treatment [8]. This was also demonstrated where patients with a history of intervention within two days [9] up to 34 days [10] had complete visual recovery. Another significant case is of a patient with the longest duration of vision loss, four years, prior to surgical intervention who had significant improvement of vision 20/400 to 20/250 following surgical intervention [11].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the size of the mass compressing the optic nerve showed a statistically significant association of the size of the mass with the likelihood of improvement based on several types of reported data [13]. In contrast to previously mentioned studies that showed no significant correlation between the time of symptoms occurring to the time of surgical intervention [8][9][10][11], Carlson et al suggest that surgery outcomes may be worse if performed more than a year after the diagnosis. Although this data considers all forms of compressive neuropathy, mucoceles were considered in the analysis, and we believe more studies are required to delineate the precise effect of time elapsed from the start of the compressive mucocele symptoms to the time of surgical intervention and the pathophysiological explanation for it.…”
Section: Age (Years)mentioning
confidence: 95%